Temporal trend analysis of violence against the elderly in Brazil - Santiago, Marizângela Lissandra de Oliveira; Nunes, Renata Adele de Lima; Sena, Francisco Thiago Carneiro; Macena, Raimunda Hermelinda Maia (Seven Editora, 2023)
Notifications for violence against the elderly have been growing in Brazil since the creation of the Elderly Statute. The purpose of this study is to analyze the temporal trend of violence notifications against the elderly in Brazil. A time series analysis of the main types of violence committed against the elderly in Brazil was performed, using data from SINAN from 2009 to 2019. The results show that the number of notifications of all types of violence against the elderly increased significantly statistics, from 2009 to 2012/2013 for almost all types, and continued to rise until 2019, more discretly, but significantly for physical, psychological, neglect, financial, and repeated violence. Is concluded that the notifications of violence against the elderly have increased significantly, however, it is necessary for society and health professionals to remain alert to identify and report these cases.DOI: https://doi.org/10.56238/devopinterscie-066